Inovasi Produk dan Manajemen Kualitas Keripik Singkong Syagina Dalam Perspektif Tantangan dan Peluang - Handoko, Diki; Bawamenewi, Benedikta M.; Simaremare, Tesya Prysilia Claudia M.; Fahrozi, Gilang; Habibi, Setia Suci; Purba, Rakhmawati; Siahaan, Rumiris; Batubara, Rizki Wulanita; Roni, Shofyan (Community Service Progress, 2025)
In the midst of increasingly tight market competition, product innovation and quality management are key factors to ensure the sustainability and growth of MSMEs. Syagina Cassava Chips is one example of an MSME engaged in the processed food sector, especially cassava chips. The purpose of this activity is to identify and analyze the challenges faced by Syagina in product innovation and its impact on competitiveness in the market and to explore the quality management strategies implemented by Syagina in meeting consumer standards and competing with chip products from big brands and identifying opportunities that can be utilized by Syagina in developing product innovation and improving quality management to support business sustainability. The results of this activity show that limited financial and technological resources are the main obstacles in carrying out product innovation. However, by implementing effective quality management strategies, such as Total Quality Management (TQM) and strict quality control, Syagina Cassava Chips can ensure that the products produced meet the standards expected by consumers.